Hubungan Nilai Ujian Nasional (Nun) Mata Pelajaran Matematika Smp Dengan Hasil Belajar Siswa Pada Mata Pelajaran Mekanika Teknik Program Keahlian Gambar Bangunan Kelas XI di SMK Negeri 35 Jakarta Barat - Fitri (Jurnal Pensil : Pendidikan Teknik Sipil, 2014)
This study aims to determine the relation of National Exam Value in junior Mathematics courses with student learning outcomes in Engineering Mechanics Course at class XI majoring in drawing technique building academic year 2013/2014 SMK Negeri 35 Jakarta. The research lasted for 3 months from October to December 2014. The located of research was conducted at SMK Negeri 35 Jakarta. The population in this study were students of class XI academic year 2013/2014 majoring in engineering drawings are 51 people. The method used in this study is a method of ex post facto to obtain primary data for the variables Y and secondary data from National Exam Value for the variable X, the approach used is one shot model to research correlational. Trial questionnaire instrument conducted by 20 respondents majoring in engineering drawing class XI buildings. After the test phase results obtained valid, the number of items valid statement after test instruments is 30 statement items. Data analysis techniques starts with finding the simple linear regression equation Å¶ = 1,78 + 0,73X. While testing requirements analysis is to test the normality of the estimated regression error X over Y with Liliefors test produces a maximum of 0,119 whereas Lcount, Ltable on stage at significance level (Î±) of 0,05 obtained a value of 0,124 then obtained Lcount < Ltable or 0,119 < 0,124 thus it can be concluded that the estimated regression error X over Y is normally distributed. Significance of correlational test with correlation Product Moment formula the result coefficient correlation maximum 0,94, which means that there is a relationship between independent variable X with the dependent vriable Y. followed by testing the significance of correlation produces that (tcount = 19,29) > (ttable = 1,67) at Î±=0,05 with dk=49, This buffer is concluded that there is a relationship with the Junior National Exam Value learning outcomes Engineering Mechanics